Do GISTs Occur in Rats and Mice? Immunohistochemical Characterization of Gastrointestinal Tumors Diagnosed as Smooth Muscle Tumors in The National Toxicology Program. (July 2019) - Janardhan, Kyathanahalli S.; Venkannagari, Priyanka; Jensen, Heather; Hoenerhoff, Mark J.; Herbert, Ronald A.; Malarkey, David E.; Sills, Robert C.; Pandiri, Arun R.
The majority of the tumors in the gastrointestinal (GI) tract of rats and mice, with spindle cell morphology, are diagnosed as smooth muscle tumors (SMTs). Similarly, several decades ago human GI tumors with spindle cell morphology were also diagnosed as SMTs. However, later investigations identified most of these tumors in humans as gastrointestinal stromal tumors (GISTs). The GISTs are considered to arise from the interstitial cells of Cajal located throughout the GI tract. Positive immunohistochemical staining with CKIT antibody is a well-accepted diagnostic marker for GISTs in humans. Since there is a considerable overlap between the histomorphology of SMTs and GISTs, it is not possible to distinguish them on hematoxylin and eosin stained sections. As a result, GISTs are not routinely diagnosed in toxicological studies. The current study was designed to evaluate the tumors diagnosed as leiomyoma or leiomyosarcoma in the National Toxicology Program's 2-year bioassays using CKIT, smooth muscle actin, and desmin immunohistochemistry. The results demonstrate that most of the mouse SMTs diagnosed as leiomyoma or leiomyosarcoma are likely GISTs, whereas in rats the tumors are likely SMTs and not GISTs.